Ideational and conceptual apraxia by cerebral infarction in the left basal ganglia and right pons: a case report - Nakaya, Yuka; Hayashi, Koji; Suzuki, Asuka; Sato, Mamiko; Takaku, Naoko; Miura, Toyoaki; Hayashi, Hiromi; Hayashi, Kouji; Kobayashi, Yasutaka (Frontiers in Rehabilitation Sciences, 2026)
We report a rare and uncommon case of ideational apraxia (IA) and conceptual apraxia (CA) in a 70-year-old woman after concurrent cerebral infarctions of the left basal ganglia (BG) extending to the corona radiata and the right pons. The patient abruptly developed difficulty operating devices such as the car's gear shift and smartphone. The brain MRI on admission disclosed infarction in the area involving the left BG and right pons. During rehabilitation therapy, she exhibited features of IA and CA, including sequencing failures when using technological devices and a profound loss of functional knowledge, exemplified by an inability to recall the purpose and functions of an automated teller machine (ATM) despite prior proficiency. A testing error involved using the keyboard rather than the mouse to open a file. Behaviorally, she impulsively initiated actions and sometimes scheduled conflicting appointments. Neuropsychological testing showed preserved scores on the Mini-Mental State Examination (MMSE) and the Hasegawa Dementia Scale-Revised (HDS-R), but memory impairment was evident on the Rivermead Behavioural Memory Test (RBMT) and the Standard Verbal Paired Associates Learning Test (S-PA). The Behavioural Assessment of the Dysexecutive Syndrome (BADS) revealed marked dysexecutive symptoms, and the Clinical Assessment for Attention (CAT) indicated reduced auditory selective attention and diminished inhibitory control. Notably, the Standard Performance Test for Apraxia (SPTA) yielded normal results. Treated with antiplatelets then antihypertensives, she was discharged home four months later. Attention deficits and driving cessation persisted, but daily life was minimally affected. Although IA and CA are typically linked to left-hemisphere damage, particularly to the BG, the right pontine lesion may have contributed to the deficits, possibly through network disruption. This infarct pattern suggests a complex interplay in apraxia development and warrants further mechanistic study.